Optimizing Sensory Marketing and Brand Experience: The Case of Kajoetangan Heritage Village - Budiarti, Lina; Wijayanti, Rena Feri; Samboro, Joko (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Kajoetangan Heritage Village is a tourist destination in Malang City, East Java Province, Indonesia with a heritage concept that highlights cultural, historical and economic elements. The effective strategic actions of tourist destinations are essential to maintain relevancy amidst competition. One of the strategies that can be implemented is optimizing sensory marketing. Sensory marketing is a marketing strategy that maximizes the stimuli of various senses, namely visual, auditory, olfactory, tactile, and gustatory. This study aims to determine the role of sensory marketing on brand experience and loyalty. This study uses a quantitative approach. A total of 102 respondents who were visitors to Kajoetangan Heritage Village participated in this study utilizing purposive sampling as the sampling technique. Path analysis is used to examine the conceptual model of research. The results provide valuable insights for Kajoetangan Heritage Village to enhance loyalty through brand experience and optimized sensory marketing strategies. Furthermore, this study enriches the theoretical understanding of brand loyalty within the tourism sector by offering strategies to maintain a competitive edge. It demonstrates that marketing activities incorporating sensory stimuli, spanning visual, olfactory, auditory, tactile, and gustatory elements, the more it will enhance the brand experience, thereby fostering deeper loyalty.